2019
DOI: 10.53555/eijas.v5i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Allelopathic Potential of Acacia Nilotica L.

Abstract: Acacia nilotica. L commonly known as babul, kikar or Indian gum Arabic tree, has been recognized worldwide as a multipurpose tree. Set of experiments were conducted  for  evaluation of the allopathic effects of water extracts of  different parts (park, leaves and pods)  of  A. nilotica as well as  soil extracts  under canopy on seed germination and  seedling  development of  receptor specie (Cucumus sativus L.) under different concentration (1%, 5% and 10% ).  Inhibitory effect of the different donor plant par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…It can be said that the acacia was the only tree that had a very strong allelopathic effect on squash germination and seedling growth. Using different crops, similar findings of strong Acacia allelopathic effects were reported (Al-Wakeel et al, 2007;Alshareef & Alaib, 2018).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It can be said that the acacia was the only tree that had a very strong allelopathic effect on squash germination and seedling growth. Using different crops, similar findings of strong Acacia allelopathic effects were reported (Al-Wakeel et al, 2007;Alshareef & Alaib, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…(Hegab et al, 2016) reported that the aqueous extract of Eucalyptus reduced the water content of corn plants. (Alshareef & Alaib, 2018) indicated that treatment of cucumber seeds with the aqueous extract of Acacia trees reduced the percentage of germination, length of roots, and the fresh and dry weight of the shoots of the cucumber seedlings. The reduction in these parameters was directly proportional to the concentration of the applied aqueous extract.…”
Section: Introductionmentioning
confidence: 99%